2021
DOI: 10.1186/s12905-021-01241-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of decreased grip strength with lower urinary tract symptoms in women: a cross‐sectional study from Korea

Abstract: Background Lower urinary tract symptoms (LUTS) including frequency, nocturia, urgency, and incontinence, are common in women and cause significant discomfort in daily life. However, diagnosis and treatment of LUTS are often delayed because many patients with such symptoms do not complain to the physician of discomfort and do not seek medical attention. LUTS are known to be associated with muscle weakness. We investigated the association between grip strength and LUTS in women of different ages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…While low grip strength in women is associated with UI, 105 this SR analysis showed grip strength had increased slightly after the intervention, but not significantly.…”
Section: Discussionmentioning
confidence: 60%
“…While low grip strength in women is associated with UI, 105 this SR analysis showed grip strength had increased slightly after the intervention, but not significantly.…”
Section: Discussionmentioning
confidence: 60%
“…33 Higher neuroticism, lower extraversion and lower conscientiousness are also associated with lower muscular strength, indexed by grip strength, 34 which has been related to higher likelihood of UI. 35 Finally, the observed associations may partly reflect the different coping styles associated with these personality traits. That is, higher neuroticism, lower extraversion and lower conscientiousness may be related to less efficient coping with UI.…”
Section: Discussionmentioning
confidence: 98%
“…Higher neuroticism and lower conscientiousness, for example, are associated with higher inflammation, 32 which in turn is related to overactive bladder 33 . Higher neuroticism, lower extraversion and lower conscientiousness are also associated with lower muscular strength, indexed by grip strength, 34 which has been related to higher likelihood of UI 35 . Finally, the observed associations may partly reflect the different coping styles associated with these personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…That study was carried out only with diabetic patients and it assessed the effect of UTIs on sarcopenia. A study that included female participants with a mean age of 48.6 revealed that low HGS was an independent variable predicting urinary tract symptoms such as nocturia, incontinence, and overactive bladder [ 14 ]. According to a cohort study with a mean age of 80.1 years, although low gait speed was an independent risk factor for severe overactive bladder, HGS was not [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia increases the risk of infections in hospitalized patients, as well as in the community [ 12 , 13 ]. Hand grip strength (HGS), an important component of the diagnosis of sarcopenia, was found to decline in patients with lower urinary tract symptoms [ 14 ]. Likewise, polypharmacy, a common problem in older age due to increasing comorbidities, is a potential risk factor that negatively affects treatment efficiency in cases of LUTIs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%